Strategic Communication with Lying Costs - KARTIK, NAVIN (Review of Economic Studies, 2009)
I study a model of strategic communication between an uninformed Receiver and an informed but upwardly biased Sender. The Sender bears a cost of lying, or more broadly, of misrepresenting his private information. The main results show that inflated language naturally arises in this environment, where the Sender (almost) always claims to be of a higher type than he would with complete information. Regardless of the intensity of lying cost, there is incomplete separation, with some pooling on the highest messages. The degree of language inflation and how much information is revealed depend upon the intensity of lying cost. The analysis delivers a framework to span a class of cheap-talk and verifiable disclosure games, unifying the polar predictions they make under large conflicts of interest. I use the model to discuss how the degree of manipulability of information can affect the trade-off between delegation and communication.